Association of body weight status and socio-demographic factors with food habits among preschool children in Peninsular Malaysia - A. Karim, Norimah; Mohd Taib, Mohd Nasir; Abu Saad, Hazizi; Ibrahim, Suraya; Loh, Siow Hon; Abdul Razak, Nurliyana (Nutrition Society of Malaysia, 2014)
Introduction: Changes in children's food habits are largely attributed to changes in the family and social environment. This cross-sectional study was carried out to determine the association of socio-demographic factors with food habits among preschool children in Peninsular Malaysia. Methods: A total of 1,933 preschool children aged 4-6 years old participated in the study. Parents or guardians were interviewed on the socio-demographic characteristics and food habits of their children. Height and weight of the preschoolers were measured; BMI-for-age, weight-for-age and height-for-age were determined. Results: The mean monthly household income was RM3,610 with 59.6% of parents having attained secondary education. The prevalence of possible risk of overweight, being overweight and obesity were 3.9%, 7.9% and 8.1%, respectively while the prevalence of underweight and stunting was 8.0% and 8.4%. A majority of the preschoolers consumed breakfast, lunch and dinner every day, with the proportion of children skipping their main meals at about 15.0%. Parents' education level and household income were significantly associated with intakes of fruits, vegetables, milk and dairy products, as well as fast food. However, there was no significant association between children's body weight status and frequency of main meals intake, fruits, vegetables, milk and dairy products, and fast food intake. Conclusion: The preschoolers demonstrated moderately healthy food habits; nevertheless even at this young age, they were inclined towards fried foods, snacking and fast foods intake. Parents and guardians should play a more significant role in educating and promoting good nutrition and food habits among preschoolers.